A Flow Reactor Model Facsimile to the Trace Metal Partitioning in a Tropical Backwater System - Parayil Unnikrishnan ; Velukutty Babu ; N. Chandramohana Kumar ; S.Muraleedharan Nair ; Anu Gopinath (Environmental Forensics, 7:189-196, 2006, 2006)
This article attempts to focus on the development of a flow reactor model applicable to the partitioning of trace metals in a backwater system, called Kuttanad backwaters, a low-lying area located in the state ofKerala, on the southwest coast of the Indian Peninsula. Based on hydrographic parameters, mainly salinity characteristics, the study area (comprising of nine stations) is divided into three zones of geochemical entity.Amultivariable model based on steady-state approachwas formulated for the partitioning of trace metals in dissolved, sedimentary, and particulate compartments. The ratio between particulate and dissolved phases is taken as the state variable; using this variable auxiliary variables were obtained that are indicative of geochemical reactivity of trace metals in this tropical backwater system.